The Influence of Leadership Style and Work Environment on Employee Job Satisfaction at the Human Resources Development and Personnel Agency of South Tangerang City - Nisa, Devi Fazilatun; Hasanah (International Journal of Science and Society, 2024)
The purpose of this research is to examine the influence of leadership style and work environment on job satisfaction with a positive and significant impact, both partially and simultaneously, at the Human Resources Development and Personnel Agency of South Tangerang City. This study utilizes a quantitative research method with an associative approach. Both primary and secondary data sources were used. Data collection was conducted through questionnaires using a Likert scale method. The population consists of 47 individuals, employing a saturated sampling technique. Testing included instrument tests (validity and reliability tests), classical assumption tests (normality, heteroscedasticity, and multicollinearity tests), and employed multiple regression and the coefficient of determination (R²). Statistical tests included partial testing or t-test and simultaneous testing or F-test. Data processing was conducted using SPSS version 25. The results of this research indicate that leadership style does not significantly affect job satisfaction, while the work environment has a positive and significant effect on job satisfaction. Moreover, there is a combined influence of leadership style and work environment on job satisfaction.